Thiamine deficiency related peripheral neuropathy in peripartum women of Kashmir, India: a hospital based study - Hilal Ahmad, Sheikh; Ahmad, S. Bashir; Jan, Asma (International Journal of Advances in Medicine, 2019)
Background: Beri Beri is still seen in Asian countries due to the large-scale consumption of thiamine depleted polished rice. Thiamine deficiency related disorders are increasingly being reported from Kashmir from last two decades. Specifically, a sensorimotor axonal neuropathy occasionally develops from thiamine deficiency and may occur even without associated Wernicke’s encephalopathy. Methods: This study is a retrospective observational study. All peripartum females referred to our departments from January 2016 to December 2017 with complaints of generalized weakness and or sensory symptoms in form of paresthesias /numbness in limbs were enrolled. Clinical features, electrophysiological features, course in hospital and response to treatment in suspected thiamine deficiency related neuropathy patients were recorded. Results: Forty-three cases were included in the study. Twenty-nine patients were suspected to have nutritional neuropathy because of thiamine deficiency at the time of admission. Out of these 27 showed improvement on treatment with thiamine. Conclusions: Thiamine responsive neuropathy is common in peripartum women of this part of world. Diagnosis is usually made clinically, in at risk individuals presenting with characteristic clinical features.